Validation of new measures of arm coordination impairment in Wheelchair Rugby - Altmann, V. C.; Groen, B. E.; Groeneweg, S.; van der Weijde, G.; Keijsers, N. L. W. (Journal of Sports Sciences, 2021)
This study aims were twofold: (1) to evaluate the construct validity of the Repetitive Movement Test (RMT) a novel test developed for Wheelchair Rugby classification which evaluates arm coordination impairment at five joints - shoulder, elbow, forearm, wrist and fingers - and (2), pending sufficiently positive results, propose objective minimum impairment criteria (MIC). Forty-two WR athletes with an eligible coordination impairment, and 20 volunteers without impairment completed the RMT and two clinically established coordination tests: the finger-nose test (FNT) and the spiral test (ST). Coordination deduction (CD), an ordinal observational coordination scale, currently used in WR classification, was obtained. Spearman-rank correlation coefficients (SCC) between RMT and ST (0.40 to 0.67) and between RMT and CD (0.31 to 0.53) generally supported RMT construct validity, SCC between RMT and FNT were lower (0.12-0.31). When the scores on ST, FNT and RMT from the sample of WR players were compared with the scores from volunteers without impairment, 93.5% to 100% of WR players had scores > 2SD below the mean of volunteers without impairment on the same test. In conclusion, RMT at the elbow, forearm, wrist and fingers have sufficient construct validity for use in WR. MIC were recommended with ST and RMT.